Fast Li+ Transport of Li−Zn Alloy Protective Layer Enabling Excellent Electrochemical Performance of Li Metal Anode. Issue 1 (22nd September 2020) - Deng, Jinxiang; Wang, Ying; Qu, Siji; Liu, Yuchi; Zou, Wei; Zhou, Fu; Zhou, Aijun; Li, Jingze
Abstract: Li alloy film has been developed as an advanced artificial protection layer on Li metal anode, attributed to its tight contact with Li metal and unique transportation capability of mixed ion/electron. Li + diffusion coefficient of the alloy interphase layer is crucial for Li dendrite growth and rate performance. Here, Zn thin film is sputtered on the surface of Li foil, and Li−Zn alloy buffer layer is spontaneously formed via an alloying reaction. In the process of electrochemical cycling, while Li + ions are reduced on the interface of the electrolyte and the anode, the fresh Li atoms rapidly diffuse into the alloy layer via fast ion transport channels of the mixed conductor, resulting in the formation of Li metal free surface. As a consequence, Li−Zn layer protected Li electrode can effectively suppress Li dendrite growth and mitigate the deterioration of Li metal, demonstrating the greatly promoted performance at high current density in both the liquid electrolyte and all solid‐state electrolyte systems. Abstract : No metal, no dendrite : Li metal anode is covered with Zn film via sputtering, and a Li−Zn alloy layer is spontaneously formed on the Li metal sheet via an alloying reaction. The alloy protection layer with fast ion transport can assist the reduced Li atoms diffused in the alloy layer at high current rate, resulting Li‐metal‐free surface, which can significantly suppress Li dendrite growth and improve electrochemical performance.